Integrating WeChat-based Mobile-Assisted Language Learning into College English Teaching - Min Guo; Minjuan Wang (European Alliance for Innovation (EAI), 2018)
WeChat, one of the most popular social networking tools in China, has attracted attention of educators to its pedagogical value such as its support for interactivity and real-time communications. Based on the literature review of mobile-assisted language learning (MALL) and WeChat, the paper aims to analyse the affordances of WeChat application in MALL, explore how to integrate WeChat-based Mobile-assisted Language Learning (MALL) into College English Curriculum so as to promote students' engagement in learning and to improve their learning outcomes